The in vitro effect of imipenem and ofloxacin on enzymic activity of Klebsiella strains - Hostacká, A (Folia microbiologica, 2000)
Fifty seven Klebsiella strains, viz. K. pneumoniae (28), K. planticola (19), K. oxytoca (6), K. ornithinolytica (3) and K. terrigena (1) possessed lipolytic and urealytic activity. The effect of imipenem and ofloxacin at subinhibitory concentrations (sub-MICs) on these enzymic activities of 4 strains was studied. At all the concentrations tested (mainly at 1/4 of the MICs) imipenem enhanced lipase activity manifested by cleavage of the substrate Tween 20. The effect of ofloxacin was strain- and concentration-dependent but in most cases lipolytic activity was also increased. The antibiotics practically did not affect the urease activity of the strains.
Keywords: lipasa; lidé; Lipase; Ofloxacin; thienamyciny; Thienamycins; ofloxacin; Klebsiella; Urease; Imipenem; Humans; Microbial Sensitivity Tests; mikrobiální testy citlivosti; Anti-Infective Agents; Klebsiella Infections; antiinfekční látky; infekce bakteriemi rodu Klebsiella; imipenem; ureasa